The risk factors of coronary heart disease among workers at south cimahi according to the jakarta cardiovascular score - Waskito, P.Pujo; Roslaeni, Rini; Wahyu Handini, Rida (ACTA Medical Health Sciences, 2023)
Coronary heart disease is the world’s biggest killer. It is influenced by several risk factors, such as age, gender, blood pressure, body mass index, physical activity, diabetes mellitus, and smoking habit. This study aimed to describe the level of risk factors for coronary heart disease in 10 years according to The Jakarta cardiovascular score. The research used a descriptive method with a cross sectional design. The population of the study was 45 workers in the subdistrict office of South Cimahi. Samples were taken using simple random sampling. The majority of the workers in South Cimahi sub-district are male employees aged 50-54 years old (24.44%). Four people (8.9%) in the population were classified as having hypertension. While the majority, 97.8%, had normal glucose levels. However, only four people included in the category of obesity (8.9%). 51.1% of the employees, or 23 individuals, were smokers. The average workers in the South Cimahi district office had heavy physical activity, namely 24 people (53.3%). Based on The Jakarta cardiovascular score tool, there were 13 respondents who were included in the low-risk category (28.9%), while 26 respondents (57.8%) were included in the medium-risk category, and 6 respondents (13.3%) were at the high-risk category. The Jakarta cardiovascular score ranked the majority of the sub-district office workers in South Cimahi to be in the medium-risk category of developing coronary heart disease; therefore, education and prevention are required. DOI : 10.35990/amhs.v2n1.p21-28 REFERENCE World Health Organization. The Top 10 Causes of Death. 2020. P2PTM Kementerian Kesehatan RI. Apa Itu Penyakit Jantung Koroner (PJK)? Catheterization, R. Abdul, W. Sjahranie. Hubungan Tingkat Pengetahuan dan Kecemasan Pasien. 2020; 2(1):1–7. Pujowaskito P, dkk. P2PTM Kementerian Kesehatan RI. Hari Jantung Sedunia: Jantungmu adalah Jantung Kami Juga. 2019. Kementerian Kesehatan Republik Indonesia. Situasi Kesehatan Jantung. 2014. Dinas Kesehatan Kota Cimahi. Profil Kesehatan Kota Cimahi Tahun 2019. Dinas Kesehatan Kota Cimahi. Profil Kesehatan Kota Cimahi Tahun 2018. Badan Pusat Statistik Kota Cimahi. Kota Cimahi Dalam Angka 2021. BPS Kota Cimahi; 2021. Kecamatan Ceppu. Tugas dan Fungsi Kecamatan. 2021. Kementerian Kesehatan RI. Peringatan Hari Jantung Sedunia 2021: Jaga Jantungmu untuk Hidup yang Lebih Sehat. Nadzir M, Prasetyo A, Fakultas Kedokteran UNEJ. Prediksi Penyakit Jantung Koroner pada PNS Melalui Metode Framingham Risk Score di RSUD dr. Soebandi Jember. 2015. Tiksnadi BB, Afrianti R, Sofiatin Y, Ridha A, Fihaya FY, Roesly RMA, dkk. Gambaran Profil Risiko Kardiovaskular Berdasarkan Skor. Yusvita F, Nandra NS. Deskripsi Tingkat Risiko Penyakit Jantung dan Pembuluh Darah pada Pekerja di PT. Forum Ilmiah X. 2018; 15. Kementerian Kesehatan. Pedoman Pengendalian Faktor Risiko Penyakit Jantung dan Pembuluh Darah. 2016; 98:64–72. Sari YA, Widiastuti, Fitriyasti B. Gambaran Faktor Risiko Penyakit Jantung Koroner di Poliklinik Jantung RSI Siti Rahmah Padang Tahun 2017-2018. 2021. Saraswati D, Lina N. Faktor Risiko Penyakit Jantung di Masyarakat pada Pos Pembinaan Terpadu (Posbindu) Puskesmas Cibeureum. Jurnal Ilmu Kesehatan Masyarakat Gorontalo. 2020; 4(1):1–7. P2PTM Kementerian Kesehatan RI. Apa Definisi Aktivitas Fisik? Rondonuwu R, Tuegeh J, Bahuwa S, Sisfiani D. Aktivitas Fisik dan Penyakit Jantung Koroner. 2020; 1(1):34–41. Yuliani F, Oenzil F, Iryani D. Hubungan Berbagai Faktor Risiko terhadap Kejadian Penyakit Jantung Koroner pada Penderita Diabetes Melitus Tipe 2. Jurnal Kesehatan Andalas. 2014; 3(1):37–40. Savia FF, Mato Rusni S. Pengaruh Merokok terhadap Kejadian Penyakit Jantung Koroner (PJK) di RS dr. Wahidin Sudirohusodo. 2013. Umar F. Perilaku Merokok dan Lingkungan Tempat Tinggal Pasien Rawat Jalan Penyakit Jantung Koroner di Makassar. Media Gizi Masyarakat Indonesia. 2011; 1.